Agility extent evaluation for mass customised product manufacturing using interval-valued fuzzy sets. (17th January 2012) - Mishra, Swagatika; Samantra, Chitrasen; Datta, Saurav; Mahapatra, Siba Sankar
In today's business scenario, enterprises have become more concerned towards mass customisation (MC) providing a wide variety of products that satisfy customers' specific requirements. Enormous product variety invites escalating costs and complexity in manufacturing context. In order to respond to the mass customisation trend, it is felt indeed necessary to develop an agility-based manufacturing system to embrace the traits involved in MC. Agility index of mass customisation and the management and technology dimension associated with the specific system are really helpful to deal with the critical elements of implementing MC. To this end, the present reporting highlights on an MC product manufacturing agility evaluation approach based on the characteristics of MC product manufacturing and the requirement of agile manufacturing, by considering: Interval-valued fuzzy sets (IVFS) have been adopted in this evaluation model. A fuzzy agility index (FAI) has been computed and compared with predefined agility measurement scale to assess the extent of agility in MC product manufacturing.